Gerenciamento de resultados contábeis: estudo sobre o comportamento discricionário das empresas do Brasil após a adoção das IFRS - CONCEIÇÃO, Eliane Silva (2016)
This work has the main objective to verify if there was a change in the level of earnings management in the Brazilians state-owned companies after the introduction of international standards – IFRS. Initially, it was presented the concept of agency theory, stakeholder theory, earnings management, discretionary accruals and IFRS- International Financial Reporting Standard. Then, after the literature review, we collected the data from the financial statements of Brazilian companies through the Economática® database for the pre IFRS (2004-2007), hybrid (2008-2009) and post IFRS periods (2010-2014). Kang regression and Sivaramakrishnan (KS) models were used to analyze the management results by accrual, the actual management models at the level of selling, general and administrative (SG&A) and production levels (PROD). In terms of results, it found that there was no change in the level of earnings management in the Brazilians state-owned company (except financial institutions), after its adoption of International Financial Reporting Standards (IFRS).